Towards Next-Generation Glucose Sensors: Reactively Sputtered Nanostructured Nickel Nitrides for CMOS Integration - Filippo Franceschini; Catarina Fernandes; Irene Taurino (Proceedings)
A facile and clean-room compatible approach to Ni nitride (NixNy) synthesis is proposed, based on a reactive sputtering deposition technique. NixNy thin films were deposited at different N2 partial pressures, after which their electrocatalytic properties towards glucose oxidation were investigated. Relative to the bare Ni, NixNy thin films sputtered at low N2 partial pressures exhibited a decreased linear range (0–5 mM) and sensitivity. Contrarily, NixNy thin films sputtered at high N2 partial pressures displayed an increase in sensitivity of ≈30% in the same linear range (0–10 mM) as for Ni. The NixNy films showed a clear morphological change from a flat thin film (Ni) to a faceted nanostructure whose characteristic dimensions decreased with increasing N2.